PTU-263 Profiling humoral immune responses to clostridium difficile-specific antigens by protein microarray. (22nd June 2015) - Negm, O; Hamed, M; Abbott, E; Tighe, P; Shone, C; Loscher, C; Edwards, L; Wilcox, M; Monaghan, TM
Abstract : Introduction: The main objective of this study was to develop, validate and implement a novel microarray platform to enable the simultaneous quantification of systemic IgG immune responses to a 7-plex panel of highly purified C. difficile -specific virulence factors, including whole toxins A and B (toxinotype 0, strain VPI10463, ribotype 087), recombinant fragments of toxin A and B, PCR ribotype-specific surface layer proteins (001, 002, 027) and control proteins (tetanus and candida). We evaluated the performance of the microarray technique against tradional ELISA. Method: Microbial antigens were diluted to 200 μg/ml in printing buffer in a 384-well plate and spotted in quadruplicate onto poly-L-Lysine-coated slides using a Biorobotics MicroGridII arrayer. The slides were blocked with 5% BSA diluted in PBS-Tween-20 wash buffer. After washing, all slides were incubated with sera diluted 1:500 in antibody diluent. Following washing, slides were incubated with biotinylated anti-human IgG diluted 1:20, 000, washed and then incubated with Streptavidin Cy5 diluted 1:2, 000 in 5% BSA. After final washes, slides were dried by centrifugation and scanned using a GenePix 4200AL scanner. The resultant TIFF images were processed with Axon GenePix Pro-6 microarray image analysis software. Protein signals were finally determined with background subtraction using RPPanalyzer, a module within the R statistical language on CRAN (http://vran.r-project.org). Kruskall Wallis was used with Dunn's post test. Correlation was evaluated using Spearman rank correlation coefficient. P values of < 0.05 were considered statistically significant. Results: A total of 327 serum samples from patients with C. difficile infection (CDI), cystic fibrosis (CF) and healthy controls (HC) were tested by microarray for the presence of specific IgG antibody. The microarray assay fell within acceptable limits of precision for both intra- and inter-assay variability for all antigens tested (<10% CV). Additionally, there was significant correlation ( p < 0 .0001) between antibody detection levels using the microarray system and the ELISA format. Conclusion: This is the first reported use of protein microarray to assess serum immunoreactivities to C. difficile -specific antigens. Our results suggest that the microarray platform allows accurate, precise and reproducible specific antibody quantifcation. Additional modifications of this approach could be used to simultaneously study multiple isotype specificities to several C. difficile strain-specific antigens for large collections of patient sera. Disclosure of interest: O. Negm: None Declared, M. Hamed: None Declared, E. Abbott: None Declared, P. Tighe: None Declared, C. Shone: None Declared, C. Loscher: None Declared, L. Edwards: None Declared, M. Wilcox Grant/ Research Support from: Multiple therapeutic and diagnostic companies, Consultant for: Multiple therapeutic and diagnostic companies, T. Monaghan: None Declared.